2015
DOI: 10.1177/0309133315615802
|View full text |Cite
|
Sign up to set email alerts
|

How do soil properties affect alpine treelines? General principles in a global perspective and novel findings from Rolwaling Himal, Nepal

Abstract: Little is known about how soil properties control tree growth at its upper limit. This paper reviews the state of knowledge and discusses the results specifically related to ecozones, to the scale-dependent importance of single factors, and to new findings from a near-natural treeline ecotone in Rolwaling Himal, Nepal. This paper identifies gaps in literature and shows where new research is needed, both conceptual and geographical. The review shows that at a global scale and throughout diverse ecozones, growin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 133 publications
1
45
0
5
Order By: Relevance
“…The small increase in average atmospheric temperature has not yet impacted species distribution in this ecotone, although it has been noted in other regions (Matteodo et al 2013;Parmesan and Yohe 2003; Telwala et al 2013). However, reduced intensity of land use (Müller et al 2015) may also have synergistic effects with increased warming in the RLI area (Morueta-Holme et al 2015).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The small increase in average atmospheric temperature has not yet impacted species distribution in this ecotone, although it has been noted in other regions (Matteodo et al 2013;Parmesan and Yohe 2003; Telwala et al 2013). However, reduced intensity of land use (Müller et al 2015) may also have synergistic effects with increased warming in the RLI area (Morueta-Holme et al 2015).…”
Section: Discussionmentioning
confidence: 85%
“…In the GCA, the practice of collecting dead tree branches and lopping signs were observed mainly in the dense forest at lower elevations. It is a near-natural or climatic treeline in this area (Müller et al 2015;Schickhoff et al 2014). …”
Section: Land Usementioning
confidence: 99%
“…Increasingly, the role of edaphic and geomorphic properties as primary drivers of treeline dynamics is being recognized (e.g., Brown & Vellend, , Macias‐Fauria & Johnson, , Müller et al, , Müller et al, , Sullivan, Ellison, Mcnown, Brownlee, & Sveinbjörnsson, ). Correspondingly, in our analysis of the relative importance of soil, predation and microsite availability on establishment potential, we found that the magnitude of the effect of soil properties was far greater than the constraints imposed by predation and microsites.…”
Section: Discussionmentioning
confidence: 99%
“…Against this background, this study performs a systematic evaluation of a 1-year WRF simulation (October 2014-September 2015) over the highly complex terrain of Khumbu (Everest) and Rolwaling Himal in terms of reproducing the spatial distribution and annual and diurnal cycles of both temperature and precipitation and, for the latter, additionally the shift in timings of the peak precipitation hour. Further, the added value of two fine-scaled (at 5 and 1 km) convection-permitting simulations was assessed relative to coarser 25 km simulation with parameterized convection, based on a dense meteorological network, including the novel observations from our TREELINE project Schwab et al, 2016;Müller et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%